Tramas comunicativas da cultura: a dança no jornalismo impresso em Manaus (1980-2000) - Freitas, Ítala Clay de Oliveira (2010)
This thesis aims to present, from a critical perspective, the relationship between dance and printed journalism in Manaus, from 1980 to 2000. The corpus of analysis is based on the following newspapers: A Crítica, Jornal do Commércio, A Notícia and Amazonas em Tempo. The time lapse has been chosen and defined by the relevance of the events at that time, as they included the strengthening of private schools of ballet and jazz dance, the increase of dance activities at schools and neighborhoods and some significant changes on artistic public policies. The thesis analyses the dance and cultural journalism as constitutive elements of a complex communicative network. The main hypotheses states that the non existence of a reflective, researcher and critical cultural journalism helped to create cultural invisibilities, making the hegemonic aesthetic and epistemological models stronger through its lack of capacity to give visibility to new propositions showed by the actual dance groups. This ideological journalism exempted the creation of a more close conversation with dancing and their specialized ways of constructing knowledge. To develop the hypotheses, the thesis works with the communication concepts that emphasize the process of mediation and the social, cultural and political constructions. It is a belief that this might constitute a path that would activate new readings of manauara culture. In this sense, the contribution of theory has built itself through various readings such as Boaventura Santos (2006,2007), Giorgio Agamben (2002,2009) and Jesús Martín-Barbero (2004), Helena Katz and Christine Greiner (2005,2010), as well as thinkers from the amazonic region on anthropology and human geography, precisely quoted throughout the thesis. The expected result is to present an analysis of a vicious circle, confined to invisibility in and outside Manaus, due to an inefficient traffic of mediations between the manauara cultural journalism and the local dance, that ended up being unfolded, blocking any social transformation on that sector